From Retribution to Restoration: Human Rights-Based Legal Protection for Women Victims of Sexual Violence - Yuliartini, Ni Putu Rai; Hartana, Hartana; Kbarek, Lukas Norman; Monteiro, Seguito (Jurnal Media Hukum, 2025)
This study examines the protection of women victims of sexual violence through a human rights-based lens, stressing the urgency of shifting from retribution to restoration. Sexual violence threatens physical security and constitutes a profound violation of dignity and human rights, with longterm psychological, social, and economic consequences. Thus, protection should not only punish perpetrators but also restore victims’ dignity and empower them. Utilizing normative legal methods, including statutory, conceptual, and case-based approaches, this research examines both national and international legal frameworks. At the national level, attention is given to Law No. 12 of 2022 on Sexual Violence and Law No. 39 of 1999 on Human Rights, both serving as key foundations for protecting justice and human rights in Indonesia, while internationally, key references include the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and the Declaration on the Elimination of Violence against Women. Several high-profile Indonesian cases are reviewed to highlight the persistent gap between comprehensive norms and weak enforcement. Findings reveal barriers, including limited awareness among law enforcement, social stigma, and inadequate support services. The study concludes that a restorative, human rights-based legal framework is crucial to ensure victim-centered justice, strengthen recovery, and foster inclusive cultural transformation beyond punitive measures.